Handbook of contamination control in microelectronics : principles, applications, and technology - Tolliver, Donald L. (Materials science and process technology series., 1988)
Covers the basics of contamination control for the beginner, while also focusing in depth on critical issues of process engineering and circuit manufacturing for the more advanced reader. Stresses to readers that what makes the area of contamination control unique is its ubiquitous nature, across all facets of semiconductor manufacturing. Clean room technology, well-recognized as a fundamental requirement in modern day circuit manufacturing, barely scratches the surface in total contamination control.